Frühmittelalterliche Studien (De Gruyter, 1967)
The yearbook Frühmittelalterliche Studien is conceived as a forum of comprehensive medieval studies. It is intended to help overcome the academic division of a diverse tradition, bearing witness to the same inseparable contexts expressed in manifold ways, into the specialist research fields of a conventional subject classification.